The Effect of Differentiated Instruction on Students’ Writing Skills in Descriptive Texts at Grade Eleven of State Senior High School 1 Sei Kepayang in the 2025/2026 Academic Year - Suci Riskia Damanik; Putri Lidiana Permata Sari (Universitas Islam Sumatera Utara, 2026)
This study investigated the effect of Differentiated Instruction on students’ writing skills in descriptive texts at State Senior High School 1 Sei Kepayang during the 2025/2026 academic year. The research was motivated by students’ low achievement in writing descriptive texts and the limited use of instructional strategies that accommodate diverse learning needs. The study addressed whether Differentiated Instruction significantly improved students’ writing performance compared to conventional teaching methods. A quantitative experimental design was employed involving two groups, namely an experimental class and a control class, each consisting of 33 students. Data were collected through pre-test and post-test writing assessments and analyzed using the t-test formula. The findings revealed that the experimental class showed a substantial improvement, with the mean score increasing from 66.6 to 85.7, while the control class improved from 49.6 to 57.7. Hypothesis testing demonstrated that the t-count value (31.42) exceeded the t-table value (1.998) at the significance level of 0.05 with 64 degrees of freedom. The study concludes that Differentiated Instruction has a statistically significant positive effect on students’ writing skills in descriptive texts and can be effectively implemented to enhance students’ writing achievement.